KESADARAN DIRI MENURUT TUTUR JATISWARA: MERAJUT KEMBALI KERUKUNAN HIDUP UMAT BERAGAMA - I Komang Suastika Arimbawa; Made G. Juniartha; I Gede Dedi Diana Putra (Widya Genitri : Jurnal Ilmiah Pendidikan, Agama dan Kebudayaan Hindu, 2020)
Religious friction begins to take shape. Many cases of intolerance have occurred around us, both those arising from differences in religion and differences in beliefs, both external and internal religions. All of these cases are a big challenge for diversity and humanity. Cooperation from all components is needed to encourage awareness of each individual to respect each other, love each other, and respect each other so that they can live side by side in harmony. The "presence" of religion is needed in this situation, because in essence religious teachings are believed to show the truth to humans. Truth is the spirit of awakening man from "drunkenness". This knowledge must be understood by everyone who wants to realize awareness. With the awareness of the nature of yourself in navigating the ark of this life, it will be an opportunity to train and get used to honing goodness, so that people can feel coolness and peace. In this way, the dream of knitting back into harmony in life can be realized.